Maternal and foetal selenium concentrations and their interrelationships in Akkaraman sheep* - KARAKILCIK, A Z; AKSAKAL, M; OZGUNER, F; CAY, M; NAZIROGLU, M (The Indian Journal of Animal Sciences, 2013)
Maternal and foetal selenium concentrations in blood plasma, erythrocyte, liver and placenta were determined in 60 pregnant ewes: foetuses of these ewes were collected at slaughterhouse in Elazig. Mean selenium concentrations in the maternal plasma, erythrocytes and liver (wet weight) were 0.38, 0.82 mol/itre and 0.16 mol/kg respectively. Mean selenium concentrations in the foetal plasma, erythrocytes and liver (wet weight) were 0.30, O. 74 mol/itre and 0.55 mo/kg. respectively. In addition, mean selenium concentration in liter placenta (wet weight) was 0.62 mol/kg. Mean selenium concentrations in the maternal plasma, erythrocytes and liver were greater than the mean selenium concentrations in the foetal samples. There was a significant positive correlation between selenium values in th’e maternal plasma (P<.001), erythrocytes (P<.05). liver (P<.001) and foetal means of selenium in these samples. These results showed that selenium concentrations in the foetuses are influenced by maternal selenium status.